The Urgency of Understanding Law No. 4 of 2023 for Capital Market Legal Consultants - Rantesalu, Abraham Astral (Law Development Journal, 2024)
Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UUP2SK) was passed on January 12, 2023, aimed at strengthening the structure of the Indonesian economy, especially the financial sector. Capital market legal consultants have an important role in providing legal opinions for the public offering process and ensuring regulatory compliance. The purpose of this study is to explore the importance of understanding UUP2SK for capital market legal consultants, focusing on its role in ensuring regulatory compliance and improving service quality to clients. The research method used is the study of literature and analysis of related statutory content. The results show that a deep understanding of UUP2SK enables capital market legal consultants to provide better services to clients, as well as ensure compliance with new capital market regulations. The implication of this research is the importance of continuous training and professional development for capital market legal consultants in understanding and implementing UUP2SK effectively, thus supporting the integrity and stability of the Indonesian capital market.